GAYA BAHASA RETORIS KIASAN NOVEL NEGERI DI UJUNG TANDUK KARYA TERE LIYE - Vili Yanthi; Kahfie Nazarudin; Edi Suyanto (FKIP Universitas Lampung, 2014)
The aim of this research is to describing rhetorical style and figurative language in the story of Negeri di Ujung Tanduk written by Tere Liye. The method which used is descriptive qualitative research method. Data collection technique and analysis techniques which used was text analysis . Data source in this research is the story of Negeri di Ujung Tanduk written by Tere Liye. The results of this research are asindeton style as the most widely used of rhetorical style while litotes style and elipsis style is least used. The most widely used of figurative languange is metaphor while the least used of are allegory, eponymous, epithets, and irony. The rhetorical style and figurative languange which is was found in the story of Negeri di Ujung Tanduk written by Tere Liye appropriate as teaching material because qualified terms of selection teaching material.Penelitian ini bertujuan untuk mendeskripsikan gaya bahasa retoris dan kiasan dalam novel Negeri di Ujung Tanduk karya Tere Liye. Metode yang digunakan adalah metode deskriptif kualitatif. Teknik pengumpulan dan analisis data yang digunakan adalah analisis teks. Sumber data penelitian adalah novel Negeri di Ujung Tanduk karya Tere Liye. Hasil analisis data ditemukan gaya bahasa retoris yang paling banyak adalah asindeton dan paling sedikit litotes dan elipsis. Gaya bahasa kiasan yang paling banyak adalah metafora dan paling sedikit alegori, eponim, epitet, dan ironi. Gaya bahasa novel Negeri di Ujung Tanduk karya Tere Liye layak sebagai bahan ajar karena memenuhi syarat pemilihan bahan ajar.Kata kunci: gaya bahasa, novel, pembelajaran.